2020
DOI: 10.2196/15896
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Experiences of a Mobile Health Self-Management Approach for the Treatment of Cystic Fibrosis: Mixed Methods Study

Abstract: Background Despite a large number of clinical trials aiming at evaluating the digital self-management of chronic diseases, there is little discussion about users’ experiences with digital approaches. However, a good user experience is a critical factor for technology adoption. Understanding users’ experiences can inform the design of approaches toward increased motivation for digital self-management. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 39 publications
1
50
0
Order By: Relevance
“…But, this 46% app use doesn't take into account the learning effect of using the app: patients remembered the PERT doses needed for frequently consumed meals and consequently used the app for new/unknown meals by the end of the study. Positive results in terms of QOL are in accordance with the user experience as assessed by means of interviews with patients and parents [25] : most parents and patients were keen to use the app in the future.…”
Section: Article In Presssupporting
confidence: 71%
See 1 more Smart Citation
“…But, this 46% app use doesn't take into account the learning effect of using the app: patients remembered the PERT doses needed for frequently consumed meals and consequently used the app for new/unknown meals by the end of the study. Positive results in terms of QOL are in accordance with the user experience as assessed by means of interviews with patients and parents [25] : most parents and patients were keen to use the app in the future.…”
Section: Article In Presssupporting
confidence: 71%
“…Another limitation is the inability to determine which specific part of the app was crucial for improvement of GI QOL (PERT prediction, educational content, PWT, symptoms registration module,…). Most patients/parents did state that the enzyme calculation module and nutrition follow-up had been the most useful features [25] . The burden of using the app was limited, as no patient discontinued for that reason and a considerable number of patients wanted to continue using the app after ending the trial.…”
Section: Article In Pressmentioning
confidence: 99%
“…Learning, practicing, and acquiring these skills is particularly important in the crucial developmental–transitional period of adolescence [ 3 ]. In recent years, mHealth has been found to be useful in promoting chronic health management [ 25 ]. This proof-of-concept study demonstrated that the content, features, and functions of the Plan My C-Day mobile application operated well, and the simulations were easy to understand and complete.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of mobile applications related to health and disease management among adolescents has increased. These include applications for adolescents with chronic conditions, such as diabetes, inflammatory bowel disease, and cystic fibrosis [ 24 , 25 ]. Mobile health (mHealth) is a way to promote health by applying mobile technologies to improve health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation